2008
DOI: 10.1158/0008-5472.can-07-5743
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow X Kinase–Mediated Signal Transduction in Irradiated Vascular Endothelium

Abstract: Radiation-induced activation of the phosphatidyl inositol-3 kinase/Akt signal transduction pathway requires Akt binding to phosphatidyl-inositol phosphates (PIP) on the cell membrane. The tyrosine kinase bone marrow X kinase (Bmx) binds to membrane-associated PIPs in a manner similar to Akt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Using a second approach to assess function of Bmx in HLEC, we used an inhibitor of Bmx, LFM-A13. This drug has been shown to block Bmx signaling in HUVEC at a dose of 30 µmol/L 30. Hence, we used this concentration to pretreat HLECs for 1 hr before the Matrigel assay.…”
Section: Resultsmentioning
confidence: 99%
“…Using a second approach to assess function of Bmx in HLEC, we used an inhibitor of Bmx, LFM-A13. This drug has been shown to block Bmx signaling in HUVEC at a dose of 30 µmol/L 30. Hence, we used this concentration to pretreat HLECs for 1 hr before the Matrigel assay.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of an invasive element may account for the observed differences between the two studies. Indeed, a recent study showed some significant inhibition of HUVEC sprouting on a Matrigel bed (34). The combination of TW-37 (0.5 μM) and radiation (1 Gy) significantly inhibited endothelial cell sprouting compared to either treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…Following cold lysis buffer washes (n=3), 4X SDS sample buffer was added and then boiled for 10 min. This was then run on SDS-PAGE with anti-PY20HRP immunoblotting according as described before [24]. …”
Section: Methodsmentioning
confidence: 99%